The Impact of Inflation, Stocks, Sukuk, and Sharia Mutual Funds on Economic Growth in 2017-2023 - Achmad Wildan Zakariya; Trischa Relanda Putra (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to ascertain, at least in part: 1) The impact of inflation on the development of the national economy 2) The performance of sharia stocks and the expansion of the national economy 3) The impact of sukuk on the development of the national economy, as well as the impact of sharia mutual funds on the same, which are the third and fourth impacts 5) Correlation between the development of the national economy in 2017-2023 through inflation, sharia mutual funds, sukuk, and stocks. Bank Indonesia (BI), the Financial Services Authority (OJK), the Central Statistics Agency (BPS), and other reliable sources of information provided the population used in the study. To sort the sample based on criteria set as independent variables, the monthly data source is used once a year. Data sources include time series data published for 2017-2023, which is considered secondary data. The analysis of the data is double linear, this research strategy uses a quantitative-associative methodology. It can be concluded that inflation has a significant adverse impact on the development of the national economy (sig. 0.0001 < 0.05), indicating that increasing inflation causes economic decline, in line with Simanungkalit's (2020) research. Sharia stocks and sukuk show a positive and significant impact on the national economy, with a value of sig. 0.0021 and 0.0019 (< 0.05), respectively, which means that an increase in the instrument will increase economic growth, according to research by Radjak & Kartika (2020) and Ardi (2018).